Penerapan Akuntansi Syariah pada UMKM dalam Meningkatkan Kinerja Keuangan - Ahmad Syarwani (Jaanur Elbarik Indonesia, 2026)
Islamic accounting serves not only as a tool for recording financial transactions but also as an instrument for control and decision-making based on the principles of honesty (ṣidq), trustworthiness (amanah), justice ('adl), responsibility (mas'uliyyah), and public benefit (maslahah). Nevertheless, many MSMEs continue to face challenges in implementing Islamic accounting, including limited knowledge, inadequate human resource capabilities, and the lack of appropriate Sharia-compliant financial recording systems. This study aims to analyze the implementation of Islamic accounting in MSMEs and its contribution to improving financial performance. The study employs a qualitative approach using a library research method by reviewing books, scientific journal articles, government regulations, and other relevant literature. The data were analyzed using content analysis techniques through the processes of identifying, classifying, comparing, and interpreting previous findings from the perspective of Islamic accounting.